PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK KECANTIKAN HANASUI DENGAN PROMOSI SEBAGAI VARIABEL MODERATING PADA KONSUMEN SHOPEE DI KELURAHAN DAWUHAN SITUBONDO - As’adiyah, Bunga Banafsaj Amiratul; Karnadi, Karnadi; Sari, Rini Kartika (Fakultas Ekonomi dan Bisnis, 2024)
Eka Jaya Internasional is a company that focuses on producing facial, hair, fragrance and home care products. The company continues to innovate in creating quality products by creating the Hanasui brand. This brand has gone viral and is widely discussed by the public, especially in the Dawuhan community. So the focus of this research is on consumers of the Hanasui brand in Dawuhan Village who purchase through the Shopee e-commerce. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using Smart PLS 3.0, showed that Price had a positive but not significant effect on Purchase decisions, Product quality had a significant positive effect on Purchase decisions, Price that with Promotion moderation had a positive but not significant effect on Purchase Decisions, Product quality that with Promotion moderation had a significant negative effect on Purchase Decisions.